Implementation of Mikrotik-Ruijie Network Design Based on NDLC to Support the Learning Process at SMK LPPM RI 2 Kedungreja - Kusnana Kusnana; Nurul Fajar; Beny Riswanto (Ilmu Bersama Center, 2026)
The rapid development of information technology demands educational institutions to provide reliable and efficient network infrastructure to support digital learning processes. SMK LPPM RI 2 Kedungreja, as a vocational education institution, is required to have an adequate computer network to ensure that ICT-based teaching and learning activities can run optimally. This study aims to design and implement a computer network using Mikrotik and Ruijie devices by adopting the Network Development Life Cycle (NDLC) method, which consists of six main phases: initiation, planning, analysis, design, implementation, and maintenance. The outcome of this study includes a structured network topology design, configuration of Mikrotik routers and Ruijie switches/access points, and complete network documentation that can be directly implemented in the school environment. The designed network supports user segmentation for students, teachers, and administrative staff, bandwidth management using queue and VLAN mechanisms, basic security features such as firewall filtering and access control, and centralized monitoring through Ruijie Cloud. Post-implementation testing was conducted to evaluate the effectiveness of the proposed network design. Performance measurements were carried out under normal school operational conditions. The test results show that the network achieved an average throughput of 92–95 Mbps for wired connections and 70–85 Mbps for wireless users. Average network latency was recorded at 5–8 ms for internal access and 15–25 ms for internet access, indicating responsive network performance. Packet loss remained below 1%, demonstrating stable and reliable data transmission across the network. These results indicate that the implemented network meets acceptable quality of service (QoS) standards for educational environments. By applying the NDLC method, the network design and implementation process was carried out systematically, resulting in a more structured, efficient, and easily maintainable system. The implementation of this network is expected to significantly improve internet accessibility within the school, support smooth online teaching and learning activities, and enhance SMK LPPM RI 2 Kedungreja’s readiness in facing the challenges of educational digitalization.